Examen especial al rubro cuentas por pagar del gobierno autónomo descentralizado parroquial de Santa Rufina del cantón Chaguarpamba, provincia de Loja periodo enero a diciembre del 2013 - Mora Largo, Ayde Esperanza (2015)
The present investigation called "SPECIAL CONSIDERATION TO ITEM SELF GOVERNMENT ACCOUNTS DECENTRALISED PARISH OF SANTA RUFINA CHAGUARPAMBA CANTON , PERIOD JANUARY TO DECEMBER 2013 PAY " is structured according to the requirements and Regulations of the National University of Loja, Distance Learning mode, career Accounting and Auditing, to obtain the title of Engineering in Accounting and Auditing Accountant Auditor. Fulfilling the objectives, began with the planning phase , where the recognition of the entity was made; is continuous with planning specifies where the internal control was made according to the rules of government audit planning , using methods of questionnaire to measure the degree of reliability, the Enforcement Working evaluated sufficient information is obtained and applying appropriate testing and auditing practices ; Communicating Results in the report was prepared with the conclusions and recommendations. Among the findings detected was determined that no reconciliation of balances between major generals are realized with the auxiliary , source documentation is disorganized likewise a report of the findings what the president to consider these comments was provided recommended to provide better services to the community. Results have been reported by an executive report which includes the professional judgment and conclusions and recommendations